2021
DOI: 10.1177/17585732211056053
|View full text |Cite
|
Sign up to set email alerts
|

Indications and outcomes of glenoid osteotomy for posterior shoulder instability: a systematic review

Abstract: Background There is limited evidence examining glenoid osteotomy as a treatment for posterior shoulder instability. Methods A search of Medline, Embase, PubMed and Cochrane Central Register of Controlled Trials was conducted from the date of origin to 28th November 2019. Nine out of 3,408 retrieved studies met the inclusion criteria and quality was assessed using the Methodological Index for Non-randomized Studies tool. Results In 356 shoulders, the main indication for osteotomy was excessive glenoid retrovers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a recent systematic review, Sardar et al. 23 found that glenoid version was corrected by an average of 10° with a subsequent improvement in normal range of motion. Moreover, the overall function showed improvement as assessed by various scoring systems, including Constant-Murley, Rowe, Oxford instability, Japan Shoulder Society Shoulder Instability Scoring, and mean shoulder value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review, Sardar et al. 23 found that glenoid version was corrected by an average of 10° with a subsequent improvement in normal range of motion. Moreover, the overall function showed improvement as assessed by various scoring systems, including Constant-Murley, Rowe, Oxford instability, Japan Shoulder Society Shoulder Instability Scoring, and mean shoulder value.…”
Section: Discussionmentioning
confidence: 99%
“…They recommend that qualified shoulder surgeons should perform the glenoid osteotomy. 23 This recommendation highlights the complexity and potential risks involved in the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although glenoid bone loss may be acquired as a result of posterior instability events and lead to recurrent instability, inherited glenoid bony abnormalities in the way of pathologic retroversion or glenoid dysplasia are another potential cause of PSI. Current indications for a posterior glenoid opening wedge osteotomy include recurrent PSI in the setting of excessive glenoid retroversion, defined as retroversion ≥10 to 15° 38 . As introduced by Scott in 1967, this procedure involves performing an osteotomy of the posterior glenoid neck and placing graft to wedge the glenoid into a more anatomic version 39 .…”
Section: Pathologic Glenoid Versionmentioning
confidence: 99%
“…However, outcomes are mixed, and this procedure is rarely done in current practice. Sardar et al 33 conducted a systematic review including 356 shoulders that underwent glenoid osteotomy. Preoperatively, mean glenoid retroversion was 15° and mean correction was 10°.…”
Section: Surgical Interventionsmentioning
confidence: 99%